B85 The first use of liposomal bupivacaine in a UK NHS hospital: the future of opiate-free surgery?. (11th August 2022) - Dean, S; Dasgupta, K; Sathyanarayana, A; Gorecha, M; Mallick, E; Williams, D
Abstract : Background and Aims: The development of an opioid-free, enhanced-recovery service is the goal of many regional anaesthetists. The use of peripheral nerve blockade using traditional local anaesthetics has allowed opiate-free anaesthesia in the intra-operative period, however, patients often require opiate analgesia post-operatively with related complications 1 . We report the first use of liposomal bupivacaine (Exparel®), outside of the private sector, in a UK hospital. This allows for long-acting (>48 hrs) analgesia with minimal motor blockade after a single procedure 2 . Methods: This case series looked at the first 8 patients to receive the drug undergoing elective knee replacement surgery. All patients received spinal anaesthesia containing 0.5% Heavy Bupivacaine alongside motor sparing blocks of the knee, including the Adductor canal, nerve to Vastus Medialis, Genicular nerves and interspace between popliteal artery and capsule of the knee (IPACK). They were reviewed post-operatively and by telephone at 72 hours and 1 week post-operatively. Results: All patients in the series had adequate post-op analgesia (average scores 2/10) with no patients requiring PRN morphine over 48 hrs. There were no reported anaesthetic-related complications. All patients had good physiotherapy outcomes with early mobilisation. The majority of patients were fit for discharge within 24 hours. Overall patient satisfaction with the procedure was very high with written compliments received by the trust. Conclusions: The use of liposomal bupivacaine has demonstrated excellent outcomes on analgesia requirements, patient satisfaction and hospital length of stay. The data from this case series will be used to further develop an opiate-free orthopaedic surgery and promote further research in the use of this drug.